2011
DOI: 10.1590/s1676-06032011000400028
|View full text |Cite
|
Sign up to set email alerts
|

Observation of predation of the giant fishing spider Ancylometes rufus (Walckenaer, 1837) (Araneae, Ctenidae) on Dendropsophus melanargyreus Cope, 1877 (Anura, Hylidae)

Abstract: Abstract:We report here an observation of predation of the giant spider Ancylometes rufus on the tree frog Dendropsophus melanargyreus in a southern region of Amazonia Forest. We also reviewed the available literature on predation of this spider species on vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…The observed behavior of nocturnal predation on leaves near bodies of water and the use of chelicerae and pedipalps to hold prey coincide with the published literature on the subject for A. bogotensis, the genus Ancylometes and other members of Ctenidae (Menin et al, 2005;Barej et al, 2009;Santana et al, 2009;Maffei et al, 2010;Moura & Azevedo, 2011;Bhukal et al, 2015;Foerster et al, 2017;Pinto & Costa-Campos et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The observed behavior of nocturnal predation on leaves near bodies of water and the use of chelicerae and pedipalps to hold prey coincide with the published literature on the subject for A. bogotensis, the genus Ancylometes and other members of Ctenidae (Menin et al, 2005;Barej et al, 2009;Santana et al, 2009;Maffei et al, 2010;Moura & Azevedo, 2011;Bhukal et al, 2015;Foerster et al, 2017;Pinto & Costa-Campos et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…Small toads are potential prey and constitute an important component in the diet of many predators (Diesel et al, 2014;Rocha et al, 2014); some arthropods as chilopods, crustaceans, insects and arachnids are known to prey upon them with distinct foraging methods (Menin et al, 2005;Barej et al, 2009;Maffei et al, 2010;Moura & Azevedo, 2011;Diesel et al, 2014;Pinto & Costa-Campos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers have reported predation events involving spiders and herpetofauna in Neotropical regions (e.g. Raven 1990, Prado & Borgo 2003, Menin et al 2005, Pombal Junior 2007, Barbo et al 2009, Maffei et al 2010, Bocchiglieri & Mendonça 2010, Maffei et al 2010, Sousa & Freire 2010a, Moura & Azevedo 2011, Diniz 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The Ancylometes rufus (Walckenaer, 1837) (Araneae, Ctenidae) is a species which is widely distributed in the Amazon (HÖFER & BRESCOVIT, 2000;BRESCOVIT ET AL., 2002), in the coastal regions of the Atlantic Forest (HÖFER & METZNER, 2015) and in enclaves of the Cerrado forests (CARVALHO & AVELINO, 2010). It is a terrestrial species, often found near aquatic environments probably due to increased food supply of both invertebrates and small amphibians, reptiles and fish (MOURA & AZEVEDO, 2011;NYFFELER & PUSEY, 2014).…”
mentioning
confidence: 99%